2020
DOI: 10.1111/imm.13286
|View full text |Cite
|
Sign up to set email alerts
|

IgA binds to the AD‐2 epitope of glycoprotein B and neutralizes human cytomegalovirus

Abstract: Human IgG and IgA responses to HCMV gB and AD‐2 epitope were determined. IgG to gB dominates, and a reduced frequency of AD‐2 responses, including IgA, is observed in serum and saliva, but IgA to AD‐2 dominates in human breastmilk. Vaccination studies demonstrated that IgA to gB could be induced but that IgA to AD‐2 was only induced in sero‐positive individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
4
1
Order By: Relevance
“…That said, we note that it has been demonstrated that a bivalent AD2 antibody (but not an AD4 targeted antibody) can still neutralize HCMV infection post-binding using a similar approach [48]. This appears to be partially in contrast to our data, since we have previously shown that QG1 monoclonal antibodies used in our study are targeted against AD2 [35]. That said, here we demonstrate that our AD2 antibodies are less effective at +4 °C compared to 37 °C, but without detailed side-by-side characterization of different AD2 antibodies it is not sensible to infer too many conclusions apropos the prior study.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…That said, we note that it has been demonstrated that a bivalent AD2 antibody (but not an AD4 targeted antibody) can still neutralize HCMV infection post-binding using a similar approach [48]. This appears to be partially in contrast to our data, since we have previously shown that QG1 monoclonal antibodies used in our study are targeted against AD2 [35]. That said, here we demonstrate that our AD2 antibodies are less effective at +4 °C compared to 37 °C, but without detailed side-by-side characterization of different AD2 antibodies it is not sensible to infer too many conclusions apropos the prior study.…”
Section: Discussioncontrasting
confidence: 92%
“…To investigate whether this was HCMV37-specific, we took advantage of two monoclonal antibodies directed against AD2 that we have previously reported to neutralize HCMV infection [35]. Using the same experimental approach, we incubated HCMV with QG1 IgG and IgA monoclonal antibodies directed against the AD2 epitope as before at concentrations known to promote partial neutralization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although differences in vaccine versus native gB structure may explain differences in the antibody repertoire it does not completely explain why if AD-6 can be recognized in the context of infected cells by antibodies we rarely see these antibodies in vivo. We know from studies of AD-2 that the VDJ re-arrangement required is a rare event 27,28 . However, we and others still see 50% AD-2 reactivity in HCMV seropositive individuals [29][30][31] -much higher than the 5% we report here for AD-6.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis was designed to establish relative levels of S-and N-binding immunoglobulins contained within the NIBSC plasma preparations. We performed ELISA as described previously [15], with minor modifications. SARS-CoV-2 antigens were diluted to 1 µg/mL in PBS and coated into ELISA plate wells.…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%